METODE IDENTIFIKASI JENIS KAYU BERDASARKAN MODEL BLOK CITRA MIKROSKOPIS PENAMPANG LINTANG - , Gasim, S.Kom, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wood name or better known as wood type is the identity of a wood. Wood type identification is an activity to obtain wood names. There are many types of wood, and each has distinct quality, usage, price, legality and tax. By knowing wood types, the next process is expected to meet expectations, and stakeholders donât experience (minimize) loss from misidentification of woods, therefore knowing type or name of each wood is very important. Wood type identification is usually performed by lumber experts, but the number of lumber experts is very limited, because producing a lumber expert takes a long time and a lot of experience. One of the proposed solutions in wood identification is applying computer science, i.e. artificial intelligence. The implementation of artificial intelligence has been done by researchers before, however no one has made comprehensive method for this activity. Furthermore the accuracy level of previous studies is not satisfactory in terms of the number features used and number of wood types used. This research made a main model for wood type identification by using artificial intelligence. The model included 1) data acquisition